The properties of cement-sand brick containing different type of shredded paper as mixing ingredient - Mohd Ayaz, Mohd Abdul Nassir (2016)
Several tons per day of pulp and paper solid waste are produced by paper mills and also generated from the household worldwide. By dumping all of this waste paper in the landfill or went through the incineration process, it will cause direct adverse effect towards the environment. Utilization of waste paper in producing a new construction material is seen as one of the ways to protect the environment. This study will provide the knowledge on the properties regarding the compressive strength and flexural strength when using different type of shredded waste paper as mixing ingredient to produce cement-sand brick. There are two type of shredded waste paper were used throughout this research, which is shredded newspaper and shredded simile paper. For this research, three different types of cement sand-brick were made. For Mix 1 and Mix 2, each will contained 2x8 mm and 3x25 mm shredded simile paper as one of the mixing ingredient respectively. While for the Mix 3, it contained 2x8 mm shredded newspaper as one of the mixing ingredient. The size of the specimens produced is 200x100x72 mm (length x width x height). Air curing is used as the curing method for the specimens. The curing durations are 30 and 60 days period. This experiment revealed that the compressive and flexural strength of the cement-sand brick contained shredded waste paper increase as the curing duration become long. This experimental studies also revealed that shredded newspaper with the size of 2x8 mm is the best type and size of shredded paper to be used as partial sand replacement to produce cement-sand brick in the future.